The Gender Pay Gap in Academia: Evidence from the Beedie School of Business - Irene M. Gordon; Karel Hrazdil; Stephen Spector (Administrative Sciences, 2024)
We analyzed gender pay gap in academia using detailed performance data of all faculty members at the Beedie School of Business, Simon Fraser University, during 2012–2022. Although we initially observed a small average pay gap in favor of male academics, we found that female academics received higher remuneration compared to their male counterparts, once we controlled for research and teaching productivity, prior education and work experience, ethnicity, and various academic appointments. Our results provide an insight into possible sources of gender bias and highlight the need to control for teaching and research performance when investigating gender pay gaps.